2007
DOI: 10.1289/ehp.9481
|View full text |Cite
|
Sign up to set email alerts
|

Vermiculite, Respiratory Disease, and Asbestos Exposure in Libby, Montana: Update of a Cohort Mortality Study

Abstract: BackgroundVermiculite from the mine near Libby, Montana, is contaminated with tremolite asbestos and other amphibole fibers (winchite and richterite). Asbestos-contaminated Libby vermiculite was used in loose-fill attic insulation that remains in millions of homes in the United States, Canada, and other countries.ObjectiveThis report describes asbestos-related occupational respiratory disease mortality among workers who mined, milled, and processed the Libby vermiculite.MethodsThis historical cohort mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(87 citation statements)
references
References 21 publications
2
84
0
Order By: Relevance
“…An application of the lung cancer model to their earlier follow-up (McDonald et al, 1986) resulted in an estimate of α = 1.91 with a ratio of K L 's estimated with α = 1 to α estimated of 2.8 (Berman and Crump, 2003). Also, an analysis of the recent follow-up of a different cohort from Libby (Sullivan, 2007) estimated α = 1.5 with a ratio of K L 's of 4.6 (Table B13) McDonald et al (2004) identified 12 deaths from mesothelioma, compared to only 2 identified in their earlier follow-up. These data were analyzed for exposure response using intensity of exposure, cumulative and a type of "residence weighted" exposure.…”
Section: Libby Mt Vermiculite Minementioning
confidence: 99%
See 3 more Smart Citations
“…An application of the lung cancer model to their earlier follow-up (McDonald et al, 1986) resulted in an estimate of α = 1.91 with a ratio of K L 's estimated with α = 1 to α estimated of 2.8 (Berman and Crump, 2003). Also, an analysis of the recent follow-up of a different cohort from Libby (Sullivan, 2007) estimated α = 1.5 with a ratio of K L 's of 4.6 (Table B13) McDonald et al (2004) identified 12 deaths from mesothelioma, compared to only 2 identified in their earlier follow-up. These data were analyzed for exposure response using intensity of exposure, cumulative and a type of "residence weighted" exposure.…”
Section: Libby Mt Vermiculite Minementioning
confidence: 99%
“…Individual cumulative fiber exposure estimates (f-yr/ml) were computed from job-specific exposure estimates and work histories . Sullivan (2007) categorized person-years of follow-up into four groups according to cumulative exposure and compared the observed number of deaths from lung cancer in each group with the number expected based on age-and calendar-year-specific rates for U.S. white males. These data are reproduced in Table B13.…”
Section: Libby Mt Vermiculite Minementioning
confidence: 99%
See 2 more Smart Citations
“…The geology of asbestos and its application to identifying and managing the natural deposits is explained in Van Gosen (2007b). Several examples of occupational and environmental exposures to natural asbestos occurrences are described in Churchill and Hill (2000), Nolan and others (2001), Clinkenbeard and others (2002), Gianfagna and others (2003), Peipins and others (2003), Ross and Nolan (2003), Burragato and others (2005), Meeker and others (2006), Sullivan (2007), and Horton and others (2008). United States Federal asbestos regulations do not specifically address occupational exposures to natural occurrences of asbestos, nor do they mention every variety of asbestiform amphibole.…”
Section: What Is Asbestos?mentioning
confidence: 99%